Handbook on Hyperbaric Medicine - Mathieu, Daniel (Springer Netherlands : Imprint: Springer, 2006)
It is now ten years since the first Handbook on Hyperbaric Medicine was published. During this time there have been many major advances: our understanding of the actions of hyperbaric oxygenation, and the pathophysiological processes it engages, have been elucidated by several studies; clinical practice is becoming more scientific with the application of evidence-based medicine (EBM) principles and the appearance of a number of randomised clinical trials; various consensus-derived organisational and operational recommendations and guidelines have become normative and are now widely accepted. For the European part, these positive developments are largely due to the continuous action of the European Committee for Hyperbaric Medicine (ECHM) - the springboard of many of these initiatives. One of the most successful initiatives was the start of a specific European research action sponsored by the EU Co-operation in Science and Technology (COST) programme. The specific COST Action for hyperbaric medicine, COST B14, has been completed and, in combination with the results of a number of experimental and clinical studies performed over the last 6 years, has provided the impetus for the publication of this new Handbook. The final product is a reference document for researchers and clinicians alike, to be used both in the research laboratory and in everyday hyperbaric clinical practice. It also provides support material for teachers and will assist students in obtaining ECHM level II and III qualifications in hyperbaric medicine. This Handbook will be of excellent use for the international scientific community.